Time trends of head injuries over multiple seasons in professional male football (soccer) - Beaudouin, F.; aus der Fünten, K.; Tröß, T.; Reinsberger, C.; Meyer, T. (Sports Medicine International Open, 2019)
The present study aimed to investigate time trends of head injuries and their injury mechanisms since a rule change as monitoring may help to identify causes of head injuries and may advance head injury prevention efforts. Based on continuously recorded data from the German football magazine "kicker Sportmagazin®" as well as other media sources, a database of head injuries in the 1st German male Bundesliga was generated comprising 11 seasons (2006/07-2016/17). Injury mechanisms were analysed from video recordings. Injury incidence rates (IR) and 95% confidence intervals (95% CI) were calculated. Time trends were analysed via linear regression. Two hundred thirty-eight match head injuries occurred (IR 1.77/1000 match hours, 95% CI 1.56-2.01). There were no significant seasonal changes, expressed as annual average year-on-year change, in IRs over the 11-year period for total head injuries (p=0.693), facial/head fractures (p=0.455), lacerations/abrasions (p=0.162), and head contusions (p=0.106). The annual average year-on-year increase for concussion was 6.4% (p=0.004). Five head injury mechanisms were identified. There were no seasonal changes in injury mechanisms over the study period. The concussion subcategory increased slightly over the seasons, which may either be a result of increasing match dynamics or raised awareness among team physicians and players.